2016
DOI: 10.1002/ajpa.23057
|View full text |Cite
|
Sign up to set email alerts
|

Maternal height and its relationship to offspring birth weight and adiposity in 6‐ to 10‐year‐old Maya children from poor neighborhoods in Merida, Yucatan

Abstract: The results suggest that maternal nutritional history as reflected in short maternal stature is associated with higher body fat in children, and that male offspring are more vulnerable to intergenerational influences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Besides, results of a study that aimed to investigate the quality of maternal diet during pregnancy in a sample of women from low to middle income groups from Merida and surrounded communities, found that 51% of women started the pregnancy with excess body weight (BMI >25 kg/m 2 ) (Romero Villanueva, 2020). The notion of an increased susceptibility of boys in this sample against adverse early conditions and intergenerational influences is supported by results of a previous study in which maternal height, a proxy measure for nutritional history, was inversely associated with fat mass index, waist circumference and skinfolds in boys (Azcorra, Dickinson, & Datta Banik, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…Besides, results of a study that aimed to investigate the quality of maternal diet during pregnancy in a sample of women from low to middle income groups from Merida and surrounded communities, found that 51% of women started the pregnancy with excess body weight (BMI >25 kg/m 2 ) (Romero Villanueva, 2020). The notion of an increased susceptibility of boys in this sample against adverse early conditions and intergenerational influences is supported by results of a previous study in which maternal height, a proxy measure for nutritional history, was inversely associated with fat mass index, waist circumference and skinfolds in boys (Azcorra, Dickinson, & Datta Banik, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…Secular trend of height and improvement of leg length in terms of relative increase of knee height (lower leg length) among daughters of women representing the Maya community in Yucatan explained intergenerational influences, rural to urban migration, and substantial improvement in their living conditions (Azcorra et al 2015). Maternal short stature has been reported to be associated with higher body fat in Maya children in Merida, Yucatan (Azcorra et al 2016). Higher body fat has been found to be positively correlated with EM in girls from Merida, Yucatan (Datta Banik et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, reports on the association of EM with differential growth patterns of height and relative body dimensions (leg length and trunk length relative to height) are not available. AM has been reported to be associated with household socioeconomic factors, mother's and grandmother's childhood living conditions in Yucatan, Mexico (Azcorra et al 2018;Datta Banik and Dickinson 2016). Poor household socioeconomic status and living conditions of the Maya community in Yucatan are important factors that are responsible for poor nutrition and physical growth of children (Azcorra et al 2016(Azcorra et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, high-fertility, and by extension large households, can come with a cost for high offspring investment strategies. High fertility increases the number of children needed to be schooled, and may produce overcrowded households, which is a well-known indicator of multi-dimensional inequality in Mexico, and is associated with low asset wealth and poor household conditions [ 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%